Chemical flocculation treatment of palm oil mill effluent (POME). - Abdul Karim, Mohamad Ismail (1986)
The use of various inorganic salts and polymers on the reduction of pollutant in palm oil mill effluent (POME) at different pH levels was investigated. Using inorganic salt treatment alone was not effective in reducing the total suspended solids (TSS) of the POME. The POME at pH5 treated with 80-100 mg/l of Magnofloc LT22 polymer was effective in coagulation and flocculation of the TSS, inducing 93-94% reduction of the suspended solids. The chemical oxygen demand (COD), total solids (TS) and turbidity of the effluent was reduced by 63%, 53% and 94% respectively. Combination treatment of 200-300mg/L FeCl(3) with 70-100 MG/l Magnafloc LT22 polymer effectively reduced the TSS of the POME (pH5) by 92-94%. The TSS of POME can be substantially reduced by treatment of the coagulating and floccculating agents before discharging it into other treatment systems or waterways. The recovered treated sludge of the POME can be used as a source of fertilizer or supplemental feed material for animals.